Investigations on the use of limitations to freedom of religion or belief in Brazil - Alves Pinto, Thiago (Religion and human rights, 2020)
The present article analyses cases from top Brazilian courts and has received contributions from several scholars, practitioners, and public officials to better understand the use of limitations to freedom of religion or belief in the country. The Brazilian Constitution provides for the right to freedom of religion or belief as a fundamental right, and other domestic legislation regulate the right, including those implementing international human rights treaties that Brazil has ratified. These laws are easily accessible. Nevertheless, domestic courts seldom rely on such international instruments or the case-law of international bodies in their judgments. Therefore, although these instruments are in force in Brazil, domestic courts do not expressly use or refer to the clauses of permissible limitations of the relevant international and regional human rights instruments, creating a scenario with low levels of legal certainty for those seeking the protection of the right to freedom of religion or belief.